Upaya Guru Akidah Akhlaq dalam Menumbuhkan Kecerdasan Spiritual Siswa MA Nurul Hidayah Al Amin Indraloka Jaya Tubaba - Ghufron, Hammam Mustofa; Ali, Mahrus; Abrori, M. Sayyidul; Irhamudin, Irhamudin (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2023)
The problem that often occurs in the era of globalization education in Indonesia is the lack of religious knowledge, one of the factors is the neglect of Islamic religious values in the learning process and the lack of student morals. The research is qualitative research. While the type of research is descriptive in nature. This research is classified as field research when viewed from the place where the research was carried out. The subjects in this study were school principals, Islamic Religious Education teachers, and students of ma nurul hidayah al-amin indraloka jaya. While the object is coaching in growing students' spiritual intelligence. The data comes from observation interviews and documentation. In this case the researcher acts as a full participant, where the researcher is a planner, implementer, data collector, analyzer and becomes a reporter on research results. The results of the study show that the efforts of the akhlaq aqidah teacher in cultivating the spiritual intelligence of students at MA Nurul Hidayah Al Amin Indraloka Jaya lead to the formation of morals through religious activities, habituation and learning in the classroom. Religious activities at MA Nurul Hidayah Al Amin Indraloka Jaya are considered very effective, because the activities carried out at school are habits that are intended as provisions to deepen faith, broaden knowledge about Islam and form Muslim and Muslim women who are able to filter out negative influences from their environment and become a young generation who good morals in everyday life.